A comparative study on the chemo-enzymatic upgrading of renewable biomass to 5-Hydroxymethylfurfural. (1st December 2020) - Saikia, Kongkona; Rathankumar, Abiram Karanam; Ramachandran, Krishnakumar; Sridharan, Harshini; Bohra, Pranay; Bharadwaj, Nikhil; Vyas, Anisha; Kumar, Vaidyanathan Vinoth
ABSTRACT: 5-hydroxymethylfurfural (HMF) obtained from renewable biomass-derived carbohydrates is a potential sustainable substitute to petroleum-based building blocks. In the present work, we constituted a comparative study on the production of HMF from two widely available real biomasses in India- Agave americana and Casuarina equisetifolia . In the initial hydrolysis studies for the production of reducing sugars, 649.5 mg/g of fructose was obtained from the hydrolysis of 5% (w/v) A. americana biomass by the enzyme inulinase in 3 h at 50°C. Similarly, upon hydrolysis of 15% (w/v) C. equisetifolia biomass by the lignocellulolytic enzymes (laccase, cellulase and xylanase) from Trichoderma atroviride, 456.65 mg/g of reducing sugars was released in 24 h at 30°C. Subsequently, the dehydration of the obtained reducing sugars to HMF was achieved with titanium dioxide as the catalyst. The dehydration of A. americana- derived fructose at 140°C led to a maximum HMF yield of 92.6% in 15 min with 10% catalyst load. Contrarily, upon optimizing the process parameters for dehydration of C. equisetifolia derived reducing sugars, the maximum HMF yield of 85.7% was obtained at 110°C in 25 min with a TiO2 concentration of 10%. This study reports for the first time the utilization of C. equisetifolia biomass for HMF production and thus, by utilizing these inexpensive, abundantly available and highly functionalized polysaccharides, a strategical approach can be developed for the production of fine chemicals, eliminating the need of fossil-based chemicals. Implications : The catalytic upgrading of lignocellulosic biomass into high-valued platform chemicals like 5-Hydroxymethylfurfural (HMF) implies an extremely significant challenge to the attempts of establishing a green economy. Casuarina equisetifolia and Agave americana represents a sustainable feedstock for the production of HMF through catalytic integration. The present work describes a two-step reaction process where the initial depolymerization step comprises of an enzymatic hydrolysis followed by a chemical-catalyst mediated dehydration process. The utilization of a biocatalytic approach followed by mild chemical catalyst eliminates the need of hazardous chemical conversion processes. Thus, the HMF produced via sustainable can bridge the gap between carbohydrate chemistry and petroleum-based industrial chemistry because of the wide range of chemical intermediates and end-products that can be derived from this compound.